Influence of ACPA‐positive rheumatoid arthritis on visual field testing in patients with arterial hypertension: A comparative cross‐sectional study. (2nd June 2021) - Wendelstein, Jascha; Fuchs, Barbara; Schlittgen, Sarah; Zielke, Robert; Brünner, Jeanette; Bolz, Matthias; Alten, Rielke; Erb, Carl
Abstract: Purpose: To evaluate a possible influence of anti‐cyclic citrullinated peptide autoantibodies (ACPA) ‐ positive rheumatoid arthritis (RA) on visual field (VF) testing in patients with arterial hypertension (aHT). Methods: We conducted an observational cross‐sectional study comparing patients with ACPA‐positive RA and aHT, patients with aHT and healthy subjects. Further inclusion criteria were visual acuity (VA) of 0.8 or better and age between 40 and 60 years. VF testing was performed with standard automated achromatic perimetry (SAP), short wavelength automated perimetry (SWAP) (Octopus 300 ® ) and flicker perimetry (Pulsar ® ). Results were analysed for a possible correlation with blood pressure or RA‐activity. Results: Twenty subjects with RA and aHT, 26 patients with aHT and 22 healthy participants were examined. Significant differences were found for mean sensitivity (MS) in SWAP comparing RA‐patients with healthy participants (ΔMS −3.06, p  = 0.001) and with hypertensive patients (ΔMS −2.32, p  = 0.007). In SAP we observed a significant difference between patients with RA and healthy subjects regarding loss variance (LV) (ΔLV = +9.77, p  = 0.004). Flicker perimetry did not demonstrate significant differences between groups. A correlation of VF changes with blood pressure level or RA‐activity was not observed. Conclusion: Patients with ACPA‐positive RA and aHT showed significant impairment of VF performance in SWAP compared to patients with aHT alone and healthy subjects. SAP also revealed a significant difference of LV between RA‐patients and healthy subjects. aHT does not seem to induce functional changes in VF testing alone.